2018
DOI: 10.15171/jcs.2018.003
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Fluid Regime Adherence in Chronic Kidney Disease Patients

Abstract: Introduction: Patients with Chronic Kidney Disease (CKD) needs to modify their lifestyle chiefly focusing on diet and fluid intake as the prognosis of these patients largely depends on adherence to the recommended nutritional regime. Non adherence to the suggested diet and fluids regime leads to rapid worsening of the condition. Methods: Cross sectional survey was conducted to determine the level of adherence to the dietary and fluids restriction among CKD patients. Inclusion criteria’s was, age between 18- 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 12 publications
2
34
0
9
Order By: Relevance
“…To date, the majority of the published studies have focused mainly on the effect of nutritional supplements such as prebiotics and probiotics to improve gut health and symptoms in individuals with CKD or kidney stones. Unfortunately, these types of therapies add further to the pill burden for this patient group [80] and have produced inconsistent results in either case [81][82][83][84]. Clinical trials that explore the effects of dietary components, such as dietary fibre in other clinical conditions are emerging [85].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of the published studies have focused mainly on the effect of nutritional supplements such as prebiotics and probiotics to improve gut health and symptoms in individuals with CKD or kidney stones. Unfortunately, these types of therapies add further to the pill burden for this patient group [80] and have produced inconsistent results in either case [81][82][83][84]. Clinical trials that explore the effects of dietary components, such as dietary fibre in other clinical conditions are emerging [85].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, adherence to diet prescription was low among these patients who were all aware of the recommended foods for their health condition. Awareness of the foods and preparation methods [36]. Non-adherence to diet prescriptions is a critical shortcoming among CKD patients, and this pattern is apparent in studies reported from developed countries where more than half of adults on hemodialysis do not adhere to their diet prescriptions [10,14,16,21,37].…”
Section: Discussionmentioning
confidence: 99%
“…28,29,31,32 Hemodiyaliz tedavisi uygulanan bireylerde sıvı alımı, diyet ve ilaç yönetimine uyumsuzluk, bireylerde birçok komplikasyonun görülmesine, mortalite ve morbiditede artışa neden olmaktadır. 5,8 Bireylerde sıvı alımında uyumsuzluk, ciddi sonuçlara yol açabilecek kronik sıvı yüklenmesine bağlı sol ventrikül hipertrofisi, bilişsel işlevlerde bozulmaya yol açmaktadır. 5,33 Diyet bileşenlerinden fosfat alımında uyumsuzluk sekonder hiperparatiroidizme, renal osteodistrofiye ve koroner arter hastalığına, potasyum alımında uyumsuzluk ventriküler aritmi ve mortalitede artışa, sodyum alımında uyumsuzluk ise total TABLO 2: Alfabetik sıraya göre derlemeye dahil edilen randomize kontrollü çalışmaların özellikleri.…”
Section: Dâhi̇l Edi̇len çAlişmalarin Gi̇ri̇şi̇mleri̇ni̇n öZelli̇kleri̇unclassified
“…3,4 Literatürde, bireylerin sıvı alımına uyumsuzluğu %22-70, diyet uyumsuzluğu %24-84, ilaç yönetimine uyumsuzluğu ise %22-56 olarak bildirilmiştir. [3][4][5][6][7][8] Hemodiyaliz tedavisi uygulanan bireylerde sıvı alımı, diyet ve ilaç yönetimine uyumsuzluk, kardiyovasküler hastalıklara, kemik demineralizasyonuna, metabolik bozukluklara, pulmoner ödeme ve mortalitede artışa yol açmaktadır. 5,6,9,10 Ayrıca uyum sorunları, bireylerin fiziksel, ruhsal ve ekonomik yönden sorun yaşamasına ve yaşam kalitelerinin olumsuz etkilenmesine neden olabilmektedir.…”
unclassified
See 1 more Smart Citation